An Empirical Study on Factors Effecting the Job Satisfaction of Employees in the Hospitality Industry – A Case of Danang City, Vietnam - Phuong, Tran Thi Kim; Vinh, Tran Trung (Asian Journal of Empirical Research, 2017)
This paper examined the factors affecting the job satisfaction of employees in the hospitality industry, by developing a conceptual model and applying it to a specific context – Danang City, Vietnam. Questionnaire data were collected from 315 employees working in the hospitality industry, Danang city. The results of empirical tests using a structural equation model support all the research hypotheses. The results indicate that job satisfaction is influenced by workplace environment; pay and promotion potential; fairness and workplace relationships. Finally, the speciﬁc theoretical and managerial implications of the results are discussed.